The Role of Law in Facing Asymmetric Warfare Through Illicit Drug Trafficking in Indonesia - Beny Abukhaer Tatara (Institute Of computer Science (IOCS), 2023)
Illicit drug trafficking is a global problem that spreads widely and causes extraordinary negative impacts. Illicit drug trafficking was be used as asymmetric warfare. The UN Convention of 1961 on Narcotic Drugs and Psychotropic Substances sets the international standards for drug regulation, and in Indonesia it is governed by the Law No.35 of 2009 on Narcotics. This research uses qualitative analysis method, with data collection technique in the form of literature study. The purpose of this research is to analyze the role of law in asymmetric warfare through illicit drug trafficking. The results of this research shows that the role of law in asymmetric warfare through illicit drug trafficking is related to : first, drug eradication, law provides the legal basis for law enforcement to take action against illicit drug traffickers. Second, legal channel regulation, law can be used to regulate and control legal channels that are used to provide drugs needed for medical and research purposes. Third, international sanctions, law can be used to take action against countries or groups that are suspected of being involved in the drug trade. Fourth, rehabilitation and recovery, law can be used to provide legal basis for rehabilitation and recovery programs for drug victims, both individuals or society.